2003
DOI: 10.1182/blood-2002-09-2761
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant factor VIIa enhances deposition of platelets with congenital or acquired αIIbβ3 deficiency to endothelial cell matrix and collagen under conditions of flow via tissue factor–independent thrombin generation

Abstract: A novel approach to treat bleeding episodes in patients with Glanzmann thrombasthenia (GT) and perhaps also in patients receiving ␣ IIb ␤ 3 inhibitors is the administration of recombinant factor VIIa (rFVIIa). The mechanism of action of rFVIIa in these patients is, however, still unclear. We studied the effect of rFVIIamediated thrombin formation on adhesion of ␣ IIb ␤ 3 -deficient platelets under flow conditions. Adhesion of ␣ IIb ␤ 3 -deficient platelets to the extracellular matrix (ECM) of stimulated human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 32 publications
4
75
0
7
Order By: Relevance
“…Red cells were isolated from whole blood from healthy volunteers who had blood group O as described previously. 17 Platelets were isolated from three patients with cirrhosis and three controls according to previously published methods. 17 After the final washing step, platelets from patients or controls were resuspended in pooled normal plasma or in pooled cirrhosis plasma.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Red cells were isolated from whole blood from healthy volunteers who had blood group O as described previously. 17 Platelets were isolated from three patients with cirrhosis and three controls according to previously published methods. 17 After the final washing step, platelets from patients or controls were resuspended in pooled normal plasma or in pooled cirrhosis plasma.…”
Section: Methodsmentioning
confidence: 99%
“…17 Platelets were isolated from three patients with cirrhosis and three controls according to previously published methods. 17 After the final washing step, platelets from patients or controls were resuspended in pooled normal plasma or in pooled cirrhosis plasma. The platelets were mixed with red cells to obtain reconstituted blood with a platelet count of 200,000/ L and a hematocrit of 40%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of thrombosis with use of Factor VII in patients with Glanzmann thrombasthenia is present in the literature (12,13). Factor VII acts by increasing subendothelial fibrin production (14). Although Factor VII is an efficient treatment in GT, care should be taken in terms of possible side effect (thrombosis etc.)…”
Section: Table 2 Frequency Of Cutaneous and Mucossal Bleedingsmentioning
confidence: 99%
“…Platelet TF may become 'de-encrypted' following its transfer via microparticles from monocytes (Rauch et al, 2000), but non-activated platelets have inactive TF on their surface which becomes active upon shedding (Siddiqui et al, 2002), and recent data (Muller et al, 2003) suggest that microvesicle-associated TF is functional in the presence of neutrophils. Lisman et al (2003) demonstrated that the adhesion of washed Gp IIb/IIIa-blocked platelets to subendothelial matrices under flow conditions was restored in the presence of 25 nmol/l rFVIIa. Platelets were shown to bind rFVIIa under these conditions.…”
Section: Discussionmentioning
confidence: 94%